THE ANALYSIS OF SOCIAL MEDIA MARKETING’S OUTCOME WITH HOSPITAL SIZE AS MODERATOR - Fauzi, Luthfi Faishal (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Many small hospital emerge after Covid-19 and face similar problem (e.g. competition). RSE one of new and small hospital in Bandung City that establish in 2020 and already face a tough competitor within area which RSAI (bigger hospital). Social media marketing become a tool to compete in this digital era. This study examines the activity of social media marketing particularly from content marketing aspect, and its effect on hospital brand loyalty. Methodology that being used in this study was quantitative which gives empirical and relevant results for marketer. Respondents profile will be shown from descriptive analysis results and the interconnected results between variables will be shown using SEM-PLS technique with WarpPLS software. This study found that bigger RSE will have better content marketing outcome toward hospital’s brand loyalty but smaller RSE will still have a chance. They could compete through emphasizing brand trust in their content marketing activities. Limited hospitals object in this study will be limitation for this research, as well as timebound and place. Next research could examine on more hospital or compared it with another city in Indonesia.. After all, this research will contribute to healthcare marketing and social media marketing science field.